PROSPECTIVE ISLAMIC LAW IN INDONESIA - Yanlua, Mohdar (Journal of Humanity, 2015)
This paper discusses the Prospective Islamic law in Indonesia. The enforcement of Islamic law in Indonesia experienced the ups and downs, ranging from the colonial period with the Government of Indonesia to the Netherlands in order to reform it.In this study it was found that a prospective law of Islam in Indonesia the development of any regime of the Government of Indonesia is experiencing developments. By the Government of Indonesia does not accept or reject the extremes, but instead selectively receive (not the totality) and gradual.Such a step is done for the sake of maintaining the stability and integrity of the country.